Characteristic Analysis of Collision Between Drill String and Well Wall. Issue 1 (January 2021) - Huang, Zhihong; Wang, Hanxiang; Lv, Xiaoxiao; Liu, Yanxin
Abstract: In order to improve the security of drilling progress and reduce the reliability impact which caused by the collision between drill string and well wall, the finite element analysis software ADINA is used to establish a finite element model to simulate the change of drill string stress after the collision between drill string and wellbore under different factors. The results show that the existence of drilling fluid with higher viscosity, lower revolution speed and autorotation speed of drill string and larger annular space is conducive to reduce the stress value caused by collision between drill string and wellbore and improve the security and stability of the drill string.